Learning other's language and culture: the personal experience from the perspectives of learning theories - Ahmad Zamri Mansor,; Ali Hassan Obaid Khalil, (Universiti Kebangsaan Malaysia, 2012)
This study concerns about teaching and learning related to the learner. The authors present their experience both as facilitators and learners in understanding Yemeni and Malay culture. To begin the discussion, the authors present the background of the concept of learning, and learning others’ language and culture. To discuss the experience, they use the key theories of humanist, social learning and constructivist. Another important model that needs to be used in adult learning is Knowles’ model of Andragogy.This model is used in order to help us to understand the core principles of adult learning: the need to know; the self-concept; experience; readiness to learn; orientation to learning; and motivation to learn.